The Effect of Morphine on the Incidence of Postoperative Nausea and Vomiting after Strabismus Surgery with Propofol - Mojtaba Rahimi Varposhti; Darioush Moradi Farsani; Masoud Fouladgar (Research Center for Rational Use of Drugs (RCRUD), 2018)
Background: Corrective strabismus surgery is associated with moderate pain and a very high incidence of postoperative nausea and vomiting (PONV). In our treatment centers Morphine is used a lot and it's associated with high incidence of PONV and we have few alternative analgesics. The aim of this study was to compare the incidence of postoperative emesis with intravenous morphine in patients undergoing corrective strabismus surgery with propofol anesthesia with the control group. Methods: In a prospective, double-blind, randomized study, 126 patients who were candidates for strabismus surgery (either sex or any age) were randomly assigned to receive morphine or placebo. None of the patients received any premedication and a standardized anesthesia technique was used for all the patients. The incidence of PONV in patients within 24 hours after the surgery was compared. Results: During 24 hours after strabismus surgery, 29 (46%) patients in the morphine group and 27 (42.9%) in the control group had nausea. The frequency of vomiting was 11 (17.5%) patients in morphine group and 9 (14.3%) in the control group. There was no significant difference between the two groups regarding nausea episodes (P=0.85) and vomiting episodes (P= 0.8). Conclusion: According to the results of this study, morphine does not increase PONV after strabismus surgery .